2020
DOI: 10.1021/acsomega.0c02099
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Pattern of Anthocyanin Accumulation during Grain Filling in Purple Waxy Corn (Zea mays L.) Suggest Optimal Harvest Dates

Abstract: Purple-corn kernels contain anthocyanins, a group of antioxidants proposed to be beneficial to human health. This study investigated the concentrations of anthocyanins and amino acids and the composition of fatty acids in the kernels of purple waxy corn (Zea mays L.) “Heukjinjuchal” during grain filling to determine when the grain nutritional value is at its highest. During grain filling, anthocyanin contents increased as the kernel color darkened. Among the anthocyanins measured, cyanidin-3-β-O-glucoside reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Therefore, the a (green/red) and b (blue/yellow) color values of the kernels could be used as indicators of carotenoid contents and polyphenol contents, respectively. In purple waxy corn, kernel color is thought to reflect anthocyanin levels [16]. Lower correlation coefficients could be caused by the greater genetic diversity of the corn samples examined in this study.…”
Section: Correlations Among Antioxidant Measurement Methods and Carot...mentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, the a (green/red) and b (blue/yellow) color values of the kernels could be used as indicators of carotenoid contents and polyphenol contents, respectively. In purple waxy corn, kernel color is thought to reflect anthocyanin levels [16]. Lower correlation coefficients could be caused by the greater genetic diversity of the corn samples examined in this study.…”
Section: Correlations Among Antioxidant Measurement Methods and Carot...mentioning
confidence: 83%
“…The two hybrids between Korean inbred lines Shinwangok and Hwandaok are cultivars developed by the National Institute of Crop Science, Korea [14,15]. All kernel samples were harvested from corn grown in the field at the NICS, Suwon, Korea (37°15′47″N, 126°59′16″E) in 2019 with field preparation performed as previously described [16].…”
Section: Plant Materialsmentioning
confidence: 99%
“…Regarding harvest time, we found that the anthocyanin content in grains of purple waxy corn reached its maximum value at 20 DAP, but the accumulation amount of anthocyanins increased gradually and reached its maximum value at 31 DAP according to regression analysis. Kim et al (Kim et al 2020) reported that the anthocyanin accumulation in purple corn occurs largely during grain lling, and the anthocyanin content in waxy corn kernels increases continuously from 15 to 31 DAP, with a sharp increase at 24 and 29 DAP. This is different in our analysis results; the reason could be the selection of different varieties.…”
Section: Reasonable Nitrogen Application and Harvest Time For Purple ...mentioning
confidence: 99%
“…Increasing levels of stearic and oleic acids from 30 to 60 DAP in corn cobs coincided with decreases in palmitic acid levels. This observation is reasonable, since palmitic acid is elongated to stearic acid, which is then converted to oleic acid by stearoyl-CoA desaturase [32]. Linolenic acid levels in kernels are a determinant of the quality of corn oils [33].…”
Section: Corn Cobs Undergo Significant Changes In Fatty Acid Composit...mentioning
confidence: 99%